Oral Crohn's disease without intestinal manifestations - Gingisetty Harikishan; Nagate Raghavendra Reddy; Harikrishnan Prasad; Subappa Anitha (Wolters Kluwer Medknow Publications, 2012)
Crohn's disease is a granulomatous inflammatory bowel disease and was described in 1932 as a chronic granulomatous disorder of the terminal ileum and is now considered a distinct member of the inflammatory bowel disease family. It may affect any part of the gastrointestinal tract. Oral Crohn's disease has been reported frequently in the last three decades with or without intestinal manifestations. In the latter case, it is considered as one of the orofacial granulomatosis. There has been much doubt whether intestinal manifestations of Crohn's disease will eventually develop in the orofacial granulomatosis. We present a female patient aged 22 years with prominent clinical findings such as persistent swelling of lower and upper lip with fissuring and angular cheilitis, granulomatous gingival enlargement, and cobblestone or corrugated appearance of labial mucosa, which are suggestive of Crohn's disease, but with no evidence of other gastrointestinal involvement. The patient underwent surgical treatment with external gingivectomy procedure. A 6-month follow-up showed minimal recurrence.